2015
DOI: 10.1002/bmc.3623
|View full text |Cite
|
Sign up to set email alerts
|

Variations in chemical fingerprints and major flavonoid contents from the leaves of thirty‐one accessions of Hibiscus sabdariffa L.

Abstract: The leaves of Hibiscus sabdariffa L. have been used as traditional folk medicines for treating high blood pressure and fever. There are many accessions of H. sabdariffa L. throughout the world. To assess the chemical variations of 31 different accessions of H. sabdariffa L., fingerprinting analysis and quantitation of major flavonoids were performed by high‐performance liquid chromatography (HPLC). The HPLC method was validated for linearity, sensitivity, precision, repeatability and accuracy. A quadrupole‐tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…A previous study on H. acetosella , investigating a different variety using a different extraction method, reported TPC and TFC levels of 1730 and 775 mg/100 g, respectively, values more than three times those found in the present study [ 19 ]. Phenolic compounds play an important role in the adaptation of plants to the environment, and their content is determined by the origin, harvesting time, and cultivation conditions [ 3 , 20 ]. Previous data has shown that the TPC and TFC contents can vary by approximately three times according to the region where the plants are collected [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study on H. acetosella , investigating a different variety using a different extraction method, reported TPC and TFC levels of 1730 and 775 mg/100 g, respectively, values more than three times those found in the present study [ 19 ]. Phenolic compounds play an important role in the adaptation of plants to the environment, and their content is determined by the origin, harvesting time, and cultivation conditions [ 3 , 20 ]. Previous data has shown that the TPC and TFC contents can vary by approximately three times according to the region where the plants are collected [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the traditional medicine of western and central Africa, decoction drinks have been prepared from extracts of the leaves and shoots because of their anti-anemic and antipyretic properties [ 1 ]. The presence of a wide variety of biochemical compounds, such as polyphenols, flavonoids, and anthocyanins have been reported in Hibiscus species [ 2 , 3 ]. Two examples, H. cannabinus and H. sabdariffa , have been studied most regarding the relationship between their biochemical compounds in the plant leaves and their biofunctional activity [ 4 , 5 , 6 , 7 ], while H. acetosella has been much less studied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in the identification of authenticity, differentiation of origin and evaluation of quality of traditional Chinese medicine and other botanical products [ 25 , 26 , 27 , 28 ]. At present, this method has been adopted by the World Health Organization and other authorities as a strategy for quality assessment of botanical products [ 18 , 29 , 30 ]. Among the chromatographic fingerprinting applied to the authentication and qualitative evaluation of botanical products over the past decade, high-performance liquid chromatography (HPLC) fingerprint emerges to be the most widely used method due to its convenience and efficiency [ 25 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Les différents composés ont été repérés et identifiés grâce à leur temps de rétention avec une détection par absorption dans l'UV-vis. Les données enregistrées ont été analysées à l'aide du logiciel MssLynx 4.1 (de Rijke et al, 2006;Wang et al, 2016).…”
Section: Identification Des Composés Par Hplc -Msunclassified